ZISWAF MANAGEMENT IN THE DEVELOPMENT OF DA'WAH PROGRAMS BASED ON SOCIAL WELFARE AT LAZ ULIL ALBAB MEDAN - Sajdah Amalia Riadi; Kustiawan, Winda (JURNAL AL-IJTIMAIYYAH, 2025)
This study aims to examine the management of zakat, infaq, and alms (ZISWAF) in the development of da'wah programs at LAZ Ulil Albab, as well as the development of da'wah programs based on social welfare. This study applies a descriptive qualitative methodology. The SWOT analysis method is used to analyze the strengths, weaknesses, opportunities, and threats faced by LAZ Ulil Albab in managing ZISWAF funds. The data used were obtained through observation, documentation, and interviews to provide a comprehensive picture of the zakat fund management process and the implementation of da'wah programs aimed at improving social welfare. The results of the study indicate that LAZ Ulil Albab has successfully managed ZISWAF funds transparently and effectively and has developed various da'wah programs that have a positive impact on the welfare of the mustahik, such as scholarships, food aid, and free medical treatment. However, there are obstacles in delivering information to the public about the need to pay zakat through institutions and the development of zakat digitalization. The findings of this study provide recommendations to LAZ Ulil Albab for the development of more targeted policies and strategies aimed at empowering the community and increasing the success of achieving the objectives of zakat in accordance with Islamic teachings and the principles of social justice.